Hidden Curriculum as Normative Organizational Control: A Qualitative Exploratory Study of Character Formation in an Indonesian Islamic Boarding School - Lola Malihah; Rini Rahmawati; Ahmad Rifani (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Research on character education in Islamic boarding schools (pesantren) has largely focused on formal curricula, while the interaction between hidden curriculum processes and organizational culture remains insufficiently examined. Addressing this gap, this study investigates how organizational culture and the hidden curriculum jointly shape students’ character at Darussalam Islamic Boarding School, Martapura, South Kalimantan, Indonesia. A qualitative case-study design was employed, using participatory observation, in-depth interviews with the kyai, teachers, and students, and document analysis. Data were analyzed through interactive thematic procedures involving data condensation, display, and verification. The findings indicate that two interconnected mechanisms primarily drive character formation. First, the hidden curriculum operates through normative control systems embedded in daily routines, disciplinary practices, and pesantren traditions, which continuously regulate and internalize expected behaviors. Second, the charismatic leadership of the kyai serves as a cultural mediator, reinforcing moral values through exemplary conduct, symbolic authority, and relational influence. These mechanisms foster the organic development of akhlakul karimah, including discipline, responsibility, obedience, and respect for teachers. This study contributes to theory by proposing an integrated perspective that links the hidden curriculum and organizational culture as mutually reinforcing dimensions of character education in Islamic educational institutions. In practice, the findings offer implications for the design of culturally grounded, value-oriented character education models that can inform educational policy and leadership practices in pesantren and other faith-based educational settings.